TANGGUNG JAWAB KURATOR ATAS KELALAIAN DALAM PENCATATAN DAFTAR HARTA PAILIT DEBITOR: Responsibility of Curator for Negligence in Recording the List of Debtor's Bankrupt Assets - Adinda Intan Amara Dewi; Sri Bakti Yunari (AMICUS CURIAE, 2025)
Bankruptcy is when the debtor loses the right to manage all of his assets, then the curator will become the debtor's guardian to complete all of the debtor's obligations. When carrying out his duties, the curator often negligently records the list of bankrupt assets by not using original receipt or document.  The identification problem is the responsibility of the curator in the event of negligence in the process of recording the list of assets of bankrupt debtors according to Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, which states that the object of the creditor's dispute can be included in the bankrupt estate by the curator can be considered as negligence of the curator in recording the list of assets of bankrupt debtors by Law concerning Bankruptcy and Suspension of Debt Payment Obligations.  Method used by the author in the research is normative, descriptive by concluding using deductive logic. The results and conclusion of this study are that curator is responsible for his negligence through Article 72 of the UUK with a claim for compensation based on Article 1365 of Civil Code and Panel of Judges should not ignore the evidence of the confession .